FARMERS’ KNOWLEDGE OF PICTORIAL INFORMATION ON AGROFORESTRY PRACTICES IN OYO STATE, NIGERIA - M. G. Olujide; O.I Oladele (Journal of Animal and Plant Sciences, 2011)
This study was carried out to determine the farmers’ knowledge of pictorial information on agroforestry practices in Ido Local Government Area of Oyo State.  A simple random sampling technique was used to select 120 farmers and data were gathered with the aid of interview guide alongside with pictures on agroforestry practices.  Data analysis was done with SPSS 13 using frequency counts, percentages and Chi-square to test the relationship between personal characteristics and knowledge of pictorial presentation. The results show that 55.8% of the respondents had no formal education while 44.2% had formal education.  About 39.2% are land owners while 60.8% got their land through borrowing and leasing.  Also, 93.3% could identify and interpret pictures on Silvopasture, 90.8% could identify and interpret pictures on Agrisilvopasture, 84.2% could identify and interpret pictures on Silvoaquaculture, and 79.2% could identify and interpret pictures on Home Garden.  Chi-square analysis showed significant relationship between personal characteristics and picture interpretation for all agroforestry practices except shelterbelts and windbreaks, silvipastoralism woodlots or plantations and live fences. It is therefore important that farmers’ characteristics are considered in the preparation of audio-visual aids in order to improve their effectiveness in transferring information to farmers.
Keywords: pictorial information; agroforestry practices; audio-visual aids; farmers; Nigeria